KEPEMIMPINAN PELAYANAN PRIMA DI PEDESAAN - Abd. Rohman (Universitas Tribhuwana Tunggadewi, 2017)
Abstract : Excellent service is one important component of all companies/organizations in order to survive in the midst of global competition. Excellent service relies on leaders in a region/region, especially Indonesia which is an agrarian country and requires the majority of the population to wrestle in the field of agriculture. So that excellent service is needed and very closely related to the application of leadership style. The results show that the implementation of excellent service leadership is generally good. Village governments are also deemed necessary to maintain timeliness, places and officers who are not rigid. While influencing factors such as education level, quality of leaders and society, facilities and infrastructure, cooperation, and clarity of bureaucratic rules. Good service provides the impact of a sense of community satisfaction and solidarity to participate in village activities. It can also improve people's welfare. However, it must be supported by a generally accepted standard, not based on the assessment of the subjectivity of village officials. This research produces a recommendation of a democratic service leadership model to improve the welfare of rural communities. This model prioritizes aspirations and participation as the basis for policy making. Implementation of this model also needs technical guidance, in order to avoid misappropriation, and can be used as a foothold and measure the extent to which the increase in welfare. Keywords: Leadership and Services Excellence Abstrak : Pelayanan Prima (service excellen) merupakan salah satu komponen penting semua perusahaan/organisasi agar tetap bertahan di tengah persaingan global. Pelayanan prima bertumpu pada pemimpin dalam suatu wilayah/daerah khususnya Indonesia yang merupakan Negara agraris dan mengharuskan mayoritas penduduknya untuk bergelut dibidang pertanian. Sehingga pelayanan prima sangat dibutuhkan dan sangat erat kaitannya dengan penerapan gaya kepemimpinan. Hasil penelitian menunjukkan bahwa implementasi kepemimpinan pelayanan prima secara umum dinilaia baik. Pemerintah desa juga dinilai perlu mempertahankan ketepatan waktu, tempat dan petugas yang tidak kaku. Sementarafaktor yang mempengaruhi diantaranya adalah tingkat pendidikan, kualitas pemimpin dan masyarakat, sarana dan prasarana, kerjasama, serta kejelasan aturan birokrasi. Pelayanan yang baik memberikan dampak rasa kepuasaan dan solidaritas masyarakat untuk berpartisipasi dalam kegiatan-kegiatan desa. Hal tersebut juga dapat meningkatkan kesejahteraan masyarakat. Namun tentunya harus didukung dengan adanya standar yang berlaku secara umum, bukan berdasarkan pada penilaian subyektifitas aparat desa. Penelitian ini menghasilkan rekomendasi model kepemimpinan pelayanan demokratis untuk meningkatkan kesejahteraan masyarakat desa. Model ini mengedepankan aspirasi dan partisipasi sebagai dasar pengambilan kebijakan. Pelaksanaan model ini juga perlu adanya petunjuk teknis, agar tidak terjadi penyelewengan, serta dapat dijadikan pijakan dan ukuran sejauh mana peningkatan kesejahteraan tersebut. Kata Kunci: Kepemimpinan dan Pelayanan Prima